2014
DOI: 10.1038/gene.2014.60
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer-associated promoter polymorphism affects akna expression levels

Abstract: Cervical cancer (CC) is responsible for >260,000 deaths worldwide each year. Efforts are being focused on identifying genetic susceptibility factors, especially in genes related to the immune response. Akna has been proposed to be one of them, but data regarding its functional role in the disease is scarce. Supporting the notion of akna as a CC susceptibility gene, we found two polymorphisms associated with squamous intraepithelial lesion (SIL) and CC; moreover, we identified an association between high akna e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Recent findings, suggest that the AT-hook transcriptional factor AKNA, could play a role in the development of CC [6]. This gene is located on chromosome 9q32, a locus of genetic susceptibility to CC [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings, suggest that the AT-hook transcriptional factor AKNA, could play a role in the development of CC [6]. This gene is located on chromosome 9q32, a locus of genetic susceptibility to CC [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed the crucial functions of AKNA in multiple physiological and pathological processes such as development, immune function, inflammation, and cancer [5,21,22]. However, the role of AKNA in GC is not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences indicated crucial function of AKNA might exert in multiple cancers. In cervical cancer, single-nucleotide polymorphisms (SNPs) make AKNA a susceptibility genetic factor [5]. AKNA directly binds the A/T-rich promoters regions of CD40 and CD40 ligand (CD40L) and coordinately regulates their expression, thereby activate antitumor immune response, while HPV E6, a cervical cancer-related oncoprotein, could downregulate AKNA and lead to the progression of cancer [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…This polymorphism has been proposed as an expression quantitative trait loci (eQTL), given that in peripheral blood mononuclear cells the A allele promotes higher expression level of AKNA [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Particularly, AKNA upregulates the expression of two costimulatory molecules, CD40 and CD40L, in T and B-lymphocytes, as well as natural killer and dendritic cells [13]. To date, AKNA gene polymorphisms as well as its expression had been associated with other human pathologies in which the immune system plays an important role such as cervical cancer [14], leukemia [15], Vogt-Koyanagi-Harada's syndrome [16], and hepatitis C virus infection [17]. …”
Section: Introductionmentioning
confidence: 99%